Mata Tak Melihat, Namun Papan Nama Berbicara: Lanskap Linguistik pada Terapis Pijat Tunanetra di Kota Malang - Dany Ardhian; Sony Sukmawan; Muhammad Hambali (Badan Pengembangan dan Pembinaan Bahasa, 2025)
This study aims to investigate the forms and patterns of language use, and informational-symbolic functions of signage employed by visually impaired massage therapists. The data source comprises 91 photographic records of signs and banners belonging to visually impaired massage practitioners across five districts (Lowokwaru, Blimbing, Sukun, Kedung Kandang, and Klojen) in Malang City, collected through field observation. Textual data were extracted from the words, phrases, and clauses appearing on these signs and banners. Data‑collection techniques included photography and transcription of all text into a corpus. For data analysis, Landry and Bourhis’s (1997) linguistic landscape framework was combined with corpus‑linguistic methods using Voyant Tools (Cirrus, StreamGraph, Trends panels) to identify lexical frequencies, collocations, and usage trends. The informational function was examined by counting seventeen types of informational signs; the symbolic function was then analysed through interpretive interviews and semantic‑corpus analysis. Findings reveal a dominance of monolingual Bahasa Indonesia (63.7 %), followed by bilingual (29.7 %) and multilingual (6.6 %) displays, reflecting both ethnic‑identity strategies and market capitalization. Core information, business name, service type, certification, contact details, prevailed in frequency. Corpus visualizations confirm a strong semantic association between “pijat” (massage) and “tunanetra” (visually impaired), as well as the emergence of symbols denoting economic self‑reliance, professionalism, and legal legitimacy. This research captures both the presence and the symbolic resistance of visually impaired therapists within Malang City’s public sphere. Abstrak Penelitian ini bertujuan menginvestigasi bentuk dan pola penggunaan bahasa serta fungsi informasi-simbolik pada papan nama terapis pijat tunanetra. Sumber data berupa 91 dokumentasi foto papan nama dan banner terapis pijat tunanetra di lima kecamatan (Lowokwaru, Blimbing, Sukun, Kedung Kandang, Klojen) di Kota Malang melalui observasi lapangan. Data teks diambil dari kata, frasa, dan klausa yang terdapat dalam papan nama dan banner. Teknik pengumpulan data meliputi fotografi dan transkripsi teks ke dalam korpus. Teknik analisis data menerapkan kerangka Lanskap Linguistik Landry & Bourhis (1997) dikombinasikan dengan linguistik korpus menggunakan Voyant Tools (panel Cirrus, StreamGraph, dan Trends) untuk mengidentifikasi frekuensi leksikal, kolokasi, dan tren penggunaan kata. Analisis fungsi informasi dilakukan dengan penghitungan 17 tipe tanda informasi; analisis simbolik dilanjutkan melalui interpretasi wawancara dan semantik korpus. Temuan menampilkan dominasi monolingual bahasa Indonesia (63,7 %), diikuti variasi bilingual (29,7 %) dan multilingual (6,6 %) yang mencerminkan strategi identitas etnis dan kapitalisasi pasar. Informasi utama berupa nama usaha, jenis layanan, sertifikasi, dan kontak mendominasi frekuensi. Visualisasi korpus menegaskan relasi semantik kuat antara “pijat” dan “tunanetra” serta emergensi simbol kemandirian ekonomi, profesionalitas, dan legitimasi hukum. Penelitian ini memotret eksistensi dan perlawanan simbolik terapis tunanetra dalam ruang publik Kota Malang.